2017
DOI: 10.1149/2.1391706jes
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Potassium-Ion Battery Anodes Derived from Waste-Tire Rubber

Abstract: The recycling of waste-tire rubber is of critical importance since the discarded tires pose serious environmental and health hazards to our society. Here, we report a new application for hard-carbon materials derived from waste-tires as anodes in potassium-ion batteries. The sustainable tire-derived carbons show good reversible potassium insertion at relatively high rates. Long-term stability tests exhibit capacities of 155 and 141 mAh g −1 for carbon pyrolyzed at 1100 • C and 1600 • C, respectively, after 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(49 citation statements)
references
References 33 publications
1
48
0
Order By: Relevance
“…Alloying of alkali metals with other elements has been regarded as a potential route to prepare high-capacity anodes for Li [55,56] Jiang and co-workers [37] Hard carbon microspheres Cohn et al [53] Graphite Carbon black + PVDF 1 m KPF 6 Xing et al [46] Poly nanocrystalline graphite Li et al [45] Tire-derived carbon Ma et al [51] P Chen et al [43] N-rich hard carbon 10% PVDF 0.8 m KPF 6 in EC:DEC -250 -180 mA h g −1 (4000 cycles at 1.8 C)…”
Section: Alloying Anodesmentioning
confidence: 99%
“…Alloying of alkali metals with other elements has been regarded as a potential route to prepare high-capacity anodes for Li [55,56] Jiang and co-workers [37] Hard carbon microspheres Cohn et al [53] Graphite Carbon black + PVDF 1 m KPF 6 Xing et al [46] Poly nanocrystalline graphite Li et al [45] Tire-derived carbon Ma et al [51] P Chen et al [43] N-rich hard carbon 10% PVDF 0.8 m KPF 6 in EC:DEC -250 -180 mA h g −1 (4000 cycles at 1.8 C)…”
Section: Alloying Anodesmentioning
confidence: 99%
“…Hexacyanometalates, known as Prussian blue analogues, can be described with a general formula of A x M[Fe(CN) 6 ] y ∙ zH 2 O (A stands for alkali ions, M represents transition metals, 0 < x < 2) . Prussian blue analogues generally have face‐centered cubic (FCC) structures within the Fm3m space group.…”
Section: Cathode Materialsmentioning
confidence: 99%
“…Thus, an appropriate host material is required to develop a fully functional cell. Recently, a study demonstrated the utilization of waste‐tires to produce anode materials for KIBs . The tire‐derived hard carbon anode could deliver a capacity of 155 mAh g −1 at C/2 after 200 cycles .…”
Section: Anode Materialsmentioning
confidence: 99%